Implementation Of Think Pair Share Learning Method In Class Viii Creed And Morals Lessons At Private Mts Darul Ulum Budi Agung Medan - Syarifah Widya Ulfa; Della Latifah Amanda; Nur Ikhsan Kharisma Sitorus; Rina Susanti; Wirda Aini Rambe (Sean Institute, 2024)
This study aims to apply the think pair share learning method in learning Akidah Morals for class VIII at MTs Swasta Darul Ulum Budi Agung Medan. This study uses a qualitative research method, with data collection techniques in the form of observation, interviews and documentation used to collect and strengthen research data. The subjects of the study were students of class VIII-2 MTs S Darul Ulum Budi Agung. With data validity techniques in the form of prolonged and lengthy, and triangulation. The results of the study showed that the implementation of the think pair share method in learning Akidah Morals in class VIII MTs Darul Ulum Budi Agung can increase students' interest in learning in class with a fairly enjoyable strategy. This learning method is believed to be able to improve student understanding, encourage active participation, and develop collaborative skills. By encouraging reflection, discussion, and presentation of understanding, the TPS method has been shown to improve student learning outcomes. Although the implementation of TPS requires the willingness, ability, and creativity of teachers in managing the classroom environment, this method is relevant in teaching values such as cooperation, respect, and responsibility. By fostering active engagement and critical thinking, the TPS method encourages a communicative learning environment that encourages students to work together to deepen understanding and build confidence in sharing ideas.